(untitled) (Research, Society and Development, 2023)
Panoramic radiography (PR) is one of the most used radiographic exams in dentistry, it analyzes bone structures such as the maxillary sinus (MS) and its extensions. The objective is to analyze in PRs, the main types of extensions in MS, such as alveolar and anterior extensions, tooth loss, relationship between tuberosity and the presence of third molars. In this cross-sectional study and quantitative, retrospective approach, by convenience sample, we verified the PRs of the Radiology Clinic of the Tiradentes University in the years 2019 and 2021, selecting patients over 18 years of age, examining 484 radiographs and 968 MWs. In the association between the variables, the non-parametric Chi-square test was used, with a statistical significance level of p<0.05. The data showed a predominance of females (63.6%) with a preminence of alveolar extensions (76.7%), and a higher prevalence in individuals aged 18 to 30 years (44%). In the affected side question, 350 alveolar extensions (79.94%) were found bilaterally, when associated with tooth loss, totaling 55.1%, however 44.9% exhibited prolongation with the presence of a tooth. The relationship between the frequency of extension to tuberosity associated with the absence of third molars totaled 79 breasts, but 45 breasts exhibited extension with third molars in the region. Therefore, there was a higher prevalence of bilateral alveolar extensions in women between 18 and 30 years of age. Regarding the presence of the third molar and extension to tuberosity, most were without the dental unit.